George Szell : a life of music - Charry, Michael (Music in American life., 2011)
Chronicles the life of George Szell, describing his accomplishments as a twentieth-century orchestra and opera conductor, and discussing his personal and musical qualities, his approach to great orchestral works and interpretation of the symphonies of Robert Schumann, and his career with the New York Philharmonic, the NBC and Chicago Symphonies, the Berlin Philharmonic, and other prestigious ensembles.